Disruption of Monocyte and Macrophage Homeostasis in Periodontitis - Almubarak, Abdulrahman; Tanagala, Kranthi Kiran Kishore; Papapanou, Panos N.; Lalla, Evanthia; Momen-Heravi, Fatemeh (Frontiers in Immunology, 2020)
Monocytes and macrophages are major cellular components of the innate immunity that play essential roles in tissue homeostasis. The contribution of different subsets of monocytes/macrophages to periodontal health and disease has not been fully elucidated. Type 2 diabetes mellitus (T2DM) is a risk factor for periodontitis. We hypothesized that the monocyte/macrophage signaling is perturbed in periodontitis-affected sites versus periodontally healthy sites and that this perturbation plays a critical role in the pathogenesis of periodontitis. Pairs of gingival tissue samples (each from a periodontally healthy and a periodontitis-affected site of the same patient) were harvested from 27 periodontitis patients, with and without T2DM. Each sample was processed to form a single-cell suspension, and a flow-cytometry panel was designed and validated to study monocyte and macrophage phenotypes. In separate experiments, the transcriptional changes associated with a pro-inflammatory phenotype were also examined in monocyte/macrophage subsets obtained from peripheral blood of patients with T2DM versus diabetes-free controls. A significantly higher proportion of intermediate (CD14+CD16+) monocytes was observed in periodontitis-affected tissues compared to healthy tissues. These monocytes overexpressed HLA-DR and PDL1 molecules, suggesting their activated inflammatory status. PDL1 increase was specific to intermediate monocytes. The ratio of M1/M2 macrophages was also significantly higher in periodontally affected sites, signifying an imbalance between inflammatory and repair mechanisms. We found a significantly higher expression of PDL1 in overall monocytes and M1 macrophages in periodontitis-affected sites compared to controls. Importantly, we identified a subpopulation of M1 macrophages present in periodontally affected tissues which expressed high levels of CD47, a glycoprotein of the immunoglobulin family that plays a critical role in self-recognition and impairment of phagocytosis. Analysis of the transcriptional landscape of monocytes/macrophages in gingival tissue of T2DM patients with periodontitis revealed a significant disruption in homeostasis toward a proinflammatory phenotype, elevation of pro-inflammatory transcription factors STAT1 and IRF1, and repression of anti-inflammatory JMJD3 in circulating monocytes. Taken together, our results demonstrate disruption of myeloid-derived cell homeostasis in periodontitis, with or without T2DM, and highlight a potentially significant role of these cell types in its pathogenesis. The impact of macrophage and monocyte signaling pathways on the pathobiology of periodontitis should be further evaluated.